Last glacial millennial-scale hydro-climate and temperature changes in Puerto Rico constrained by speleothem fluid inclusion δ18 and δ2H values - Warken, Sophie F.; Weißbach, Therese; Kluge, Tobias; Vonhof, Hubert; Scholz, Denis; Vieten, Rolf; Schmidt, Martina; Winter, Amos; Frank, Norbert (Climate of the past, 2022)
Abstract. We present speleothem fluid inclusion δ18Of and δ2Hf values from Larga Cave, Puerto Rico, that cover the interval between 46.2 and 15.3 ka on the millennial scale, including the Last Glacial Maximum (LGM) and several stadial and interstadial cycles. The data set can be divided in two main clusters of stable isotope compositions of the fluid inclusion water with respect to the global meteoric water line (GMWL), which coincide with strong variations in the water content of the stalagmite. In particular, this clustering is found to be climate related, where one cluster comprises samples from cold and dry periods, such as the Heinrich and Greenland stadials (HSs and GSs), as well as parts of the LGM, which exhibit very high δ18Of and δ2Hf values. We interpret this enrichment as being caused by evaporation inside the cave due to enhanced cave ventilation during these colder and drier times. In contrast, in most samples corresponding to warmer and wetter Greenland interstadials (GIs), but also for some from HS 2 and 3, the δ18Of and δ2Hf values plot on the meteoric water line and modification of fluid inclusion water due to “in-cave” evaporation are found to be negligible. Consequently, variations of recent glacial hydro-climate and temperatures in the western tropical Atlantic can be constrained. In general, δ18Of values from fluid inclusions are up to 3 ‰ higher than those of modern drip water, which is interpreted as a weaker atmospheric convective activity during the last glacial period. In addition, reconstructed temperatures suggest an average cooling of 2-3 ∘C during the LGM compared to modern cave temperatures. Reconstructed cave temperatures yield an average cooling of −1.4 ± 2.8 ∘C for HS 2 and −3.6 ± 2.2 ∘C for HS 3. Higher δ18Of values of these samples further suggest that the drip water was dominated by orographic rainfall and/or cold fronts, along with weak or even absent convective activity. In contrast, during interstadial phases, reconstructed temperatures reached nearly modern values, and convective activity was comparable to or only slightly weaker than today.
Gesehen am 31.03.2022